Interplay between aging, lung inflammation/remodeling, and fibronectin EDA in lung cancer progression. Issue 12 (1st December 2020) - Greenwell, John C.; Torres-Gonzalez, Edilson; Ritzenthaler, Jeffrey D.; Roman, Jesse
ABSTRACT: Lung cancer remains the leading cause of cancer death in the United States. Since most lung cancers occur in aged individuals with chronic lung disorders characterized by inflammation and/or fibrosis, we hypothesized that aging and tissue inflammation/remodeling act in concert to promote lung cancer progression. To test this, we engaged in studies using young and aged C57BL/6 mice in conjunction with bleomycin treatment in a syngeneic model of lung cancer. Wildtype young (3 months) and aged (9 months) C57BL/6 mice were injected with Lewis Lung Carcinoma (LLC) cells at day 14 after injection with phosphate-buffered saline or bleomycin. Untreated aged mice were found to develop more lung metastases than young mice. Bleomycin induced weight loss and lung inflammation/remodeling in both young and aged mice, and it increased the number of lung metastases in aged lungs, but not in young lungs. Since aged lungs show alterations in the expression of fibronectin EDA, we repeated studies in aged WT and aged FN EDA KO mice. In the absence of tissue remodeling/inflammation, WT and FN EDA KO mice developed the same number of metastases when injected with LLC cells. However, the increase in lung metastasis due to bleomycin treatment was abolished in FN EDA KO mice, but only in aged and injured lungs. Together, these studies show increased lung cancer metastasis in aging animals and point to the influence of FN EDA and injury in this process.